Reviving the “Ganges Water Machine”: where and how much? - Muthuwatta, Lal P.; Amarasinghe, Upali A.; Sood, Aditya; Lagudu, S. (Copernicus GmbH, 2017)
Runoff generated in the monsoon months in the upstream parts of the Ganges River basin (GRB) contributes substantially to downstream floods, while water shortages in the dry months affect agricultural production in the basin. This paper examines the potential for subsurface storage (SSS) in the Ganges basin to mitigate floods in the downstream areas and increase the availability of water during drier months. The Soil and Water Assessment Tool (SWAT) is used to estimate “sub-basin” water availability. The water availability estimated is then compared with the sub-basinwise unmet water demand for agriculture. Hydrological analysis reveals that some of the unmet water demand in the subbasin can be met provided it is possible to capture the runoff in sub-surface storage during the monsoon season (June to September). Some of the groundwater recharge is returned to the stream as baseflow and has the potential to increase dry season river flows. To examine the impacts of groundwater recharge on flood inundation and flows in the dry season (October to May), two groundwater recharge scenarios are tested in the Ramganga sub-basin. Increasing groundwater recharge by 35 and 65 % of the current level would increase the baseflow during the dry season by 1.46 billion m3 (34.5 % of the baseline) and 3.01 billion m3 (71.3 % of the baseline), respectively. Analysis of pumping scenarios indicates that 80 000 to 112 000 ha of additional wheat area can be irrigated in the Ramganga sub-basin by additional SSS without reducing the current baseflow volumes. Augmenting SSS reduces the peak flow and flood inundated areas in Ramganga (by up to 13.0 % for the 65 % scenario compared to the baseline), indicating the effectiveness of SSS in reducing areas inundated under floods in the sub-basin. However, this may not be sufficient to effectively control the flood in the downstream areas of the GRB, such as in the state of Bihar (prone to floods), which receives a total flow of 277 billion m3 from upstream sub-basins.